Examining the impact of value added tax on Sukuk yield: a review - Al-Otaibi, Mohammed Ibrahim; Nor, Normaziah Mohd; Yusri, Yusniyati (Universitas Islam Negeri Ar-raniry, 2024)
This study aims to explore the impact of VAT (Value Added Tax) on Sukuk market in Saudi Arabia. A systematic literature review was used to answer a clearly formulated question regarding the impact of VAT on Sukuk market. The papers author included met the following key selection criteria: 1) published in peer-reviewed journals, 2) written in English, 3) focus on only impact of VAT on Sukuk market; and 4) published from January 2010 to September 2022. Initially, a total of 1,943 articles were identified from which only 8 papers were included in this study which fulfil the inclusion and exclusion criteria. From the selected articles there was mounting evidence that there is further study required for understanding the VAT impact on Sukuk market around the world and particularly in the Kingdom of Saudi Arabia because the VAT introduces in January 2018. Furthermore, more investigation is also needed in VAT and its impact on Sukuk market in Saudi Arabia especially for achieving national development plan Vision 2030. Moreover, green Sukuk also play important role in the social and economic development of a country and more such infrastructural investment is needed.